A De Novo Frameshift Variant in SMC1A Causes Non‐Classic Cornelia de Lange Syndrome With Epilepsy: A Case Report and Literature Review - Ying Yang; Liqing Chen; Zhenzhen Wang; Yaling Ding; Yan Liu (Molecular Genetics & Genomic Medicine)
ABSTRACT Background Cornelia de Lange syndrome (CdLS) is a multisystem genetic disorder. Although individuals with variants in the SMC1A gene are less commonly seen in CdLS, they exhibit a high incidence of epilepsy and atypical phenotypic variability. Methods The clinical data of a patient with non‐classic CdLS and epilepsy caused by an SMC1A variant were summarized. A literature review was conducted to analyze the genotype–phenotype correlations and epilepsy characteristics in related cases. Results A 5‐year‐6‐month‐old female patient presented with facial features, double outlet right ventricle (DORV), and recurrent epilepsy. Whole exome sequencing (WES) identified a de novo heterozygous frameshift mutation, c.2890_2893del (p.Ser964Valfs*26), in the SMC1A gene. A review of the literature identified several characteristics of non‐classic CdLS with epilepsy caused by SMC1A variants: the majority of cases were non‐classic (81.5%), predominantly female (68.2%), with a median onset age of 11.5 months. Common features included severe/profound developmental delay (52.6%), hypotonia (18.2%), cardiovascular anomalies (36.4%), and intrauterine growth retardation (IUGR) (22.7%). Among the non‐classic cases, seizure clusters occurred in 22.7%, status epilepticus in 18.2%, and drug‐resistant epilepsy in 33.3%. Genotypes in non‐classic cases included missense mutations (40.9%), frameshift mutations (31.8%), splice site variants (9.1%), nonsense mutations (9.1%), deletions (4.5%), and truncations (4.5%). Conclusion Our study expanded the phenotypic data and mutational spectrum of non‐classic CdLS with epilepsy caused by SMC1A variants. Compared to individuals with the classic form of CdLS, the non‐classic cases appeared more frequently in females and were associated with a higher prevalence of severe/profound developmental delay and cardiovascular anomalies. In contrast, IUGR was significantly less common in non‐classic individuals. Regarding epilepsy characteristics, some individuals including seizure clusters, status epilepticus, drug resistance, and hypotonia, no significant differences were observed between classic and non‐classic cases. The predominant genotypes in non‐classic cases were missense and frameshift mutations.